Respuesta :

Answer:

Inverse of f(x)=-x^3-9 is [tex]f^{-1}(x)=\sqrt[3]{-x-9}[/tex]

Option B is correct option.

Step-by-step explanation:

We need to find inverse of [tex]f(x)=-x^3-9[/tex]

For finding the inverse replace f(x) with y

[tex]y=-x^3-9[/tex]

Now, solve for x

Adding 9 on both sides

[tex]y+9=-x^3-9+9\\y+9=-x^3[/tex]

Multiply both sides by -1

[tex]-(y+9)=x^3\\x^3=-y-9[/tex]

Taking cube root on both sides:

[tex]x^3=-y-9\\\sqrt[3]{x^3} =\sqrt[3]{-y-9} \\x=\sqrt[3]{-y-9}[/tex]

Now replace x with f^{-1}(x) and y with x

[tex]f^{-1}(x)=\sqrt[3]{-x-9}[/tex]

So, inverse of f(x)=-x^3-9 is [tex]f^{-1}(x)=\sqrt[3]{-x-9}[/tex]

Option B is correct option.

Answer:B is the answer

Step-by-step explanation:

ACCESS MORE